The Influence of The Entrepreneurial Environment And Government Support on The Performance of MSMEs in Bandung - Iskamto, Dedi; Tresnamurti, Galuh; Indrajaya, Danang (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
Entrepreneurs is an important factor in the entrepreneurial process. Entrepreneurs who are prosperous tend to continue their business, whereas entrepreneurs who are not prosperous will abandon their business. This research aims to determine the factors that influence the welfare of MSME (Micro, Small and Medium Enterprises) entrepreneurs in the city of Bandung. Entrepreneurs play a big role in improving the economy of developing countries, such as Indonesia. The research methodology used is a quantitative method where the data collective by quisenare and Smar PLS use to data calculate.. it can be concluded that Government support and the External Environment have a significant influence on MSME performance in Bandung City. Apart from that, it is known that MSME performance influences the well-being of entrepreneurs.